The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2105/ajph.2004.051870
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Health Clubs for People with Mobility Disabilities and Visual Impairments

Abstract: Persons with mobility disabilities and visual impairments have difficulty accessing various areas of fitness facilities and health clubs. AIMFREE is an important tool for increasing awareness of these accessibility barriers for people with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 19 publications
6
82
0
6
Order By: Relevance
“…7 In contrast, Rimmer et al reported that fewer than 25% of the facilities in their study were willing to adjust or pro-rate membership fees for persons with disabilities. 12 The study results indicate that none of the facilities provided training in wheelchair transfer techniques. This outcome is in stark contrast to the Rimmer et al study that indicated that 50% of the participating facilities provided training to new staff members on how to assist individuals in transferring from wheelchairs to exercise equipment or swimming pools.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…7 In contrast, Rimmer et al reported that fewer than 25% of the facilities in their study were willing to adjust or pro-rate membership fees for persons with disabilities. 12 The study results indicate that none of the facilities provided training in wheelchair transfer techniques. This outcome is in stark contrast to the Rimmer et al study that indicated that 50% of the participating facilities provided training to new staff members on how to assist individuals in transferring from wheelchairs to exercise equipment or swimming pools.…”
Section: Discussionmentioning
confidence: 89%
“…This outcome is in stark contrast to the Rimmer et al study that indicated that 50% of the participating facilities provided training to new staff members on how to assist individuals in transferring from wheelchairs to exercise equipment or swimming pools. 12 Forty-five percent of individuals with SCI report needing assistance with transfers. 6 This means that individuals with mobility impairments who may need minimal assistance to use existing facility equipment cannot do so due to lack of staff training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations